Greenland Ice sheet [in "State of the Climate in 2013"] - Tedesco, M.; Box, J.; Cappelen, J.; Fettweis, Xavier; Jensen, T.; Mote, T.; Rennermalm, A.; Smith, L.; W. van de Wal, R.; Wahr, J. (Bulletin of the American Meteorological Society, 2014)
peer reviewed